(untitled) (Marketing Journal, 2025)
The article is dedicated to analyzing the development of small business and entrepreneurship in the Qashqadaryo region through econometric modeling. The study employs regression analysis and time series methods based on statistical data of small business a nd entrepreneurship (SBE) entities in the region for the period 2000 –2024. Key factors influencing the volume of SBE products were identified, and forecast results for 2025 –2030 were developed. The study findings show that employment levels, investments, and the value of fixed assets significantly impact the product volume. The r esults confirm a stable trend in SBE development and serve as a basis for forming regional economic policy and developing practical recommendations for effective resource allocation. Econometric calculations and forecasting performed in the EViews software serve as the main scientific method of the study.